REVIEWS (New blackfriars, 1971)
Reviews in this article DANTE'S STYLE IN HIS LYRIC POETRY, by Patrick Boyde. NEW TESTAMENT THEOLOGY, Vol. I:‘The Proclamation of Jesus’, by Joachim Jeremias. THE HEAVENLY COUNSELLOR IN ISAIAH XL, 13-14, by R. N. Whybray. THE SIGN OF JONAH, by Richard A. Edwards. GOD AND THE WORLD, by Hugo Meynell. ATHEISM AND ALIENATION, by Patrick Masterson. EXPLANATION AND MEANING: An Introduction to Philosophy, by Daniel M. Taylor.